Stereotype threat and the cognitive performance of adolescent immigrants: The role of cultural identity strength - Silvana Weber; Markus Appel; Nicole Kronberger (Contemporary Educational Psychology, 2015)
In many world regions students with certain immigrant backgrounds underperform in educational settings. Theory and research suggest that this achievement gap could be partially explained by stereotype threat. Stereotype threat is a detrimental psychological state that inhibits individuals who belong to a negatively stereotyped group at times of learning and performance. The aim of this work was to examine both the influence of students' residence culture identity strength and ethnic identity strength on their cognitive performance under threat. Two experimental studies, conducted in European secondary schools, are reported. Experiment 1 (N = 132) showed that in a situation of explicit stereotype threat, high identification of immigrants with their residence culture predicted better cognitive performance, independently of ethnic identity strength. Residence culture identity strength was unrelated to cognitive performance in a control condition or a more implicit threat condition. Experiment 2 (N = 152) included an experimental manipulation of residence culture identity strength. The results show that highlighting similarities with the residence culture (vs. highlighting differences) positively influences immigrant students' performance under threat. This research connects the stereotype threat framework with acculturation research, and points at ways to increase the educational achievement of immigrant students.

The influence of stereotype threat on immigrants: review and meta-analysis - Markus Appel; Silvana Weber; Nicole Kronberger (Frontiers in Psychology, 2015)
In many regions around the world students with certain immigrant backgrounds underachieve in educational settings. This paper provides a review and meta-analysis on one potential source of the immigrant achievement gap: stereotype threat, a situational predicament that may prevent students to perform up to their full abilities. A meta-analysis of 19 experiments suggests an overall mean effect size of 0.63 (random effects model) in support of stereotype threat theory. The results are complemented by moderator analyses with regard to circulation (published or unpublished research), cultural context (US versus Europe), age of immigrants, type of stereotype threat manipulation, dependent measures, and means for identification of immigrant status; evidence on the role of ethnic identity strength is reviewed. Theoretical and practical implications of the findings are discussed.

Wer bin ich? Wie sich Facebook und Co auf unsere Selbstwahrnehmung auswirken - Constanze Schreiner; Silvana Weber (The In-Mind, 2015)
Nie war Selbstdarstellung so einfach wie heute, zu Zeiten des Web 2.0. Die NutzerInnen gestalten die Inhalte aktiv mit und haben Raum für die Darstellung ihrer eigenen Person sowie für kleinere oder größere Identitätsexperimente. Auf sozialen Netzwerkseiten erhalten wir andauerndes und unmittelbares Feedback auf die Präsentation unseres Selbst. Entgegen der Befürchtungen vieler Eltern und Pädagogen kann die (aktive) Nutzung sozialer Netzwerkseiten positive Konsequenzen für die Selbstwahrnehmung haben.

Chancen und Risiken beim Einsatz von neuen Medien in der Psychotherapie - Silvana Weber; Constanze Schreiner (Das In-Mind Magazin, 2014)
Internet und Smartphone sind heutzutage fester Bestandteil in allen Bereichen unseres Lebens. Diese Omnipräsenz legt nahe, neue Medien auch für die Übermittlung therapeutischer Interventionen und präventiver Maßnahmen bei psychischen Erkrankungen wie Depressionen oder Angststörungen zu nutzen. So könnte eine breite Masse an Menschen, die Hilfe bei psychischen Problemen benötigen, schnell, einfach und kosteneffizient erreicht werden - ganz ohne lästige Wartezeiten. Doch wie wirksam sind diese Programme wirklich und worauf muss man als NutzerIn achten?

Media and Identity - Markus Appel; Martina Mara; Silvana Weber (Media and Social Life, 2014)